BRONCHIAL ASTHMA IN CHILDREN- AN AYURVEDIC PERSPECTIVE - Anirudhan, *Roshni; Shankar, Sanitha V. (International Journal of Ayurveda and Pharma Research, 2019)
Childhood Asthma is the most common serious chronic disease in infants and children. Bronchial asthma (Swasa roga) referred to as a chronic lung disease, showcase an obstructed air pathway, which hinders the free flow of inhaled oxygenated air through the air channels in the lungs, as being inflamed, constricted and filled with mucous. Certain dietary practices and deeds/habits which both the parents and children tends to perform on a regular basis causes Kaphapitha Dushti which coupled with Aniyata Vahni (unstable digestive fire) of children, leads to Jataragni Mandya (indigestion) in children and results in the formation of Krimi (worms) in the stomach. These Krimi in turn worsens the Agnimandhya, thereby completely destabilizing the digestive and assimilative capacity of the gastrointestinal system. The Srotorodha produced by the vitiated Kapha Pitha Dosha along with Ama in the Amasaya, leads to Vataprakopa and thus a Doshic derangement happens in the Amasaya. As stated by Vagbhatacharya in Swasa Nidana, this Doshic derangement in the Amasaya, triggers a disease process in the previously indisposed, trigger awaiting Pranavaha Srotas, leading to Swasa Roga. Here in Swasa Roga, Ajeerna (indigestion) and Krimi (worms) acts as Sannikrishta Nidanas, whereas Pranavaha srotodushti act as Viprakrishta Nidana. The mainstay of treatment should be avoidance and clearance of Sannikrishta Nidanas and addressing the Viprakrishta Nidana. But most importantly, the drugs should have action over the respiratory system to strengthen and revitalize the system and make it immune and less susceptible to future attacks.